2012
DOI: 10.1371/journal.pone.0048052
|View full text |Cite
|
Sign up to set email alerts
|

The Mobilization and Recruitment of C-Kit+ Cells Contribute to Wound Healing after Surgery

Abstract: Delayed wound healing is a serious clinical problem in patients after surgery. A recent study has demonstrated that bone marrow-derived c-kit-positive (c-kit+) cells play important roles in repairing and regenerating various tissues and organs. To examine the hypothesis that surgical injury induces the mobilization and recruitment of c-kit+ cells to accelerate wound healing. Mice were subjected to a left pneumonectomy. The mobilization of c-kit+ cells was monitored after surgery. Using green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, high risk of recurrence for early-stage breast cancer patients following mastectomy has been reported in an analysis of 1,173 patients who underwent mastectomy with no subsequent adjuvant systemic therapy ( Demicheli et al., 1996 ). Mechanisms to explain distant metastasis following primary tumor resection include (1) the presence of residual tumor cells or tissue at the resected site ( Ando et al., 2003 , Minsky et al., 1988 ), (2) the recruitment of inflammatory cells and platelets to the resected site that promote wound healing and cell proliferation ( Ceelen et al., 2014 , Hofer et al., 1999 , Retsky et al., 2012 ), and (3) increased local and systemic effects that can induce an angiogenic switch in remote dormant tumors ( Bono et al., 2010 , Retsky et al., 2012 , Takemoto et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high risk of recurrence for early-stage breast cancer patients following mastectomy has been reported in an analysis of 1,173 patients who underwent mastectomy with no subsequent adjuvant systemic therapy ( Demicheli et al., 1996 ). Mechanisms to explain distant metastasis following primary tumor resection include (1) the presence of residual tumor cells or tissue at the resected site ( Ando et al., 2003 , Minsky et al., 1988 ), (2) the recruitment of inflammatory cells and platelets to the resected site that promote wound healing and cell proliferation ( Ceelen et al., 2014 , Hofer et al., 1999 , Retsky et al., 2012 ), and (3) increased local and systemic effects that can induce an angiogenic switch in remote dormant tumors ( Bono et al., 2010 , Retsky et al., 2012 , Takemoto et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to paracrine functions of BMDCs, our data suggested transplanted BMDCs activated stem cells (c-Kit-or Sca-1-positive cells) and EGFR in lingual epithelium and induced blood vessel formation in dermis. Several studies have reported that c-Kit-and/or Sca-1-positive stem cells were mobilized from the bone marrow to injured sites for wound healing (Takemoto et al, 2012); then, these recruited stem cells produced various growth factors, such as EGF or VEGF, to accelerate wound healing. In this study, activation of stem cells and EGFR was observed at early stages (2-5 d) following irradiation; then, abundant blood vessel formation in the dermis was detected just below the basement membrane at 7 d. In view of these phenomena, paracrine factors of transplanted BMDCs may function to induce endogenous stem cells to the site of tongue mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of adult stem cells intended as cell populations restricted to their own tissue has been challenged by reports indicating that these cells can be mobilized in response to a tissue damage 4 5 6 7 . A growing number of scientific reports indicates that under the influence of various pathological stimuli, tissue-specific and/or bone marrow-derived stem/progenitor cells are rapidly mobilized to the blood stream, playing a crucial role in the repair of solid organs, acting directly or enhancing the re-activation of resident stem cells 5 7 8 . Indeed, peripheral blood (PB) is an ideal alternative source for progenitor cells owing to the ease of cell retrieval and blood bank storage.…”
mentioning
confidence: 99%